A STUDY ON THE ROLE OF OPPOSITION PARTIES IN KARNATAKA POLITICS - D, Anantakumar; K, Mohan Das (International Journal of Psychosocial Rehabilitation, 2020)
Present days Bharatiya Janata Party (BJP), Indian National Congress (INC) and Janata Dal (Secular)(JDS) are the major political parties in the state. Recently BhatiyaPrajegalaKalyana Paksha added to the list. Marxist Communist Party and Maharashtra Ekikaran Samiti are the other active political parties in the state of Karnataka. The various precursors of the Janata Dal (Secular) such as Janata Party and Janata Dal had also been very influential political parties in the past years. Splinter groups such as Karnataka Congress Party (KCP),Karnataka Janta Paksha (KJP), BadavaraShramikaraRaithara(BSR) Congress, Lok Shakti and Janata Dal (United) have made considerable achievements in a few elections. Erstwhile parties which have been influential in the state include Indian National Congress (Organisation) (NCO), Bharatiya Jana sangh, Kisan Mazdoor Praja Party (KMPP), National Development Party (NDP), Praja Socialist Party (PSP), Samyukta Socialist Party (SSP), Swatantra Party and Communist Party of India (CPI). Parliamentary opposition is the permanent feature of government in party system. It prevents the centralisation of power in a person or a group of people. Without effective opposition party, no democratic government can be alive. Ruling party is essential for taking decisions and to lead the government and even opposition party also essential for confirming that, the decisions taken by the government are through the proper parliamentary discussions. Ivor Jennings Stated “Opposition Party Works as alternative government and it gives its attention on the problems of the people”. Functions of the Opposition party are important as of the functions of the ruling party or government. If there is no opposition party in the nation, there is no democracy. This research paper focussed on the study of active political parties, electoral politics and opposition parties in the state of Karnataka.